(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This comprehensive article explores the multifaceted effects of exercise on the health and well-being of preschool children, emphasizing physical, cognitive, social, and emotional development. It delves into the significance of various physical activities, the role of parental involvement, and the impact on sleep patterns, fostering a holistic understanding of the benefits of exercise during early childhood